2021
DOI: 10.1101/2021.04.01.437961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishing a Role of the Semantic Control Network in Social Cognitive Processing: A Meta-analysis of Functional Neuroimaging Studies

Abstract: Most leading models of socio-cognitive processing devote little discussion to the nature and neuroanatomical correlates of cognitive control mechanisms. Recently, it has been proposed that the regulation of social behaviours could rely on brain regions specialised in the controlled retrieval of semantic information, namely the anterior inferior frontal gyrus (IFG) and posterior middle temporal gyrus. Accordingly, we set out to investigate whether the neural activation commonly found in social functional neuroi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 198 publications
(221 reference statements)
0
16
0
Order By: Relevance
“…The overlap suggests these regions serve a domain‐general role rather than one that is specialised towards processing social information. While there is evidence for a selective role of the right TPJ and mPFC in social and moral processing (Saxe & Kanwisher, 2003; Saxe & Wexler, 2005; Young et al, 2010 ), there is also evidence that they are engaged by a wide range of tasks including those outside the social domain (Bzdok et al, 2016; Cabeza et al, 2012; Diveica et al, 2021,; Humphreys et al, 2020; Seghier et al, 2010; van Overwalle, 2009). In other recent work, we have considered the possibility that activation of frontal regions, the TPJ and pMTG during ToM tasks, also reflects engagement of domain‐general processes related to semantic cognition (Binney & Ramsey, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlap suggests these regions serve a domain‐general role rather than one that is specialised towards processing social information. While there is evidence for a selective role of the right TPJ and mPFC in social and moral processing (Saxe & Kanwisher, 2003; Saxe & Wexler, 2005; Young et al, 2010 ), there is also evidence that they are engaged by a wide range of tasks including those outside the social domain (Bzdok et al, 2016; Cabeza et al, 2012; Diveica et al, 2021,; Humphreys et al, 2020; Seghier et al, 2010; van Overwalle, 2009). In other recent work, we have considered the possibility that activation of frontal regions, the TPJ and pMTG during ToM tasks, also reflects engagement of domain‐general processes related to semantic cognition (Binney & Ramsey, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the ATL results in profound and wide‐ranging socio‐affective deficits in both primates and humans (Binney, Henry, et al, 2016; Edwards‐Lee et al, 1997; Irish et al, 2014; Klüver & Bucy, 1937; Kumfor et al, 2013; Kumfor, Hazelton, et al, 2017; Kumfor, Honan, et al, 2017; Kumfor & Piguet, 2012; Terzian & Dalle Ore, 1955). Amongst neurotypical samples, the findings of functional neuroimaging studies suggest an almost ubiquitous involvement in the high‐level processing of faces and emotions (Avidan et al, 2014; Collins et al, 2016; Collins & Olson, 2014; Ramot et al, 2019; Wong & Gallate, 2012), as well as in more abstracted forms of social processing, such as moral cognition and mental state attribution (also known as theory of mind [ToM]) (Diveica et al, 2021; Molenberghs et al, 2016; Moll et al, 2005; Schurz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to test the robustness of our meta-analytic results to baseline differences, we complemented our primary analysis with a supplementary analysis that excluded low-level contrasts (cf. Diveica et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to test the robustness of our metaanalytic results to baseline differences, we complemented our primary analysis with a supplementary analysis that excluded low-level contrasts (cf. Diveica et al, 2021). N = number of participants; fMRI = functional magnetic resonance imaging; PET = positron emission tomography; MNI = Montreal Neurological Institute space; TAL = Talairach space.…”
Section: Literature Searchmentioning
confidence: 99%
“…An extensive literature has shown that these two regions are key hubs of semantic cognition [53][54][55][56] (and more specifically of 'semantic control') as they are necessary to flexibly retrieve knowledge to suit a specific task or context (for example, to use a newspaper -canonically known for a different purposeto chase a fly). These areas are not exclusively implicated in semantic memory, but also in the cognitive control of other memory domains [57][58][59][60] (i.e., episodic memory), emotions and social processes 61 , suggesting that they may play a broader role in the cognitive control necessary for the attribution of meaning to stimuli and experiences. Also, AG showed a decrease in fingerprint.…”
Section: Discussionmentioning
confidence: 99%